Penguatan Ideologi Pancasila di Pondok Pesantren - Najib, Ivan Nove Ainun; Untari, Sri; Sukriono, Didik (Balai Diklat Keagamaan Bandung, 2024)
The purpose of this study is to outline initiatives taken at Darul Ulum Islamic Boarding School in the Sandai Subdistrict of Ketapang Regency, West Kalimantan, to enhance students' comprehension of the Pancasila doctrine. The study uses a descriptive research design and a qualitative methodology. Interviews are used as part of data gathering methods, and Pattern Matching is used to analyze the data. The study's findings show that the pupils have received formal education, which is taught to them at their individual school levels, in an effort to improve their comprehension of Pancasila doctrine. In order to develop people with a solid grasp of religious knowledge, non-formal education also plays a significant role. It focuses on areas that are prioritized for students throughout their time at the boarding school. Hadith doctrines, theology, jurisprudence, ethics, and Qur'anic interpretation are a few examples. These courses are taught with the goal of making sure that students acquire strong moral, social, and personal standards as well as information, particularly in the area of religious studies. Therefore, both formal and informal education are used in an effort to increase students' comprehension of the Pancasila concept. Keywords: Pancasila Ideology; Islamic Boarding School; Nationalism.